A stainless steel chromium-tantalum alloy material, a stainless steel soaking plate, and a preparation method and application thereof

By forming a chromium alloy layer on stainless steel thermal plates, the problem of insufficient hardness and corrosion resistance of the existing average thermal plate material is solved, and a thinner and durable average hot plate is achieved, and its service life is extended.

CN116103554BActive Publication Date: 2025-01-24BEIJING COOLJET TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211310803.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-01-24
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The existing heat-smoothing plate materials such as copper or copper alloys are difficult to use in ultra-thin electronic products due to low hardness, difficulty in thickness, and poor corrosion resistance. The vacuum degree of stainless steel heat-smoothing plates is reduced due to hydrogen evolution with water. Ineffective.

Method used

Using stainless steel chromium-tantalum alloy material, by forming a chromium-tantalum alloy layer on the surface of the stainless steel, chromium elements and tantalum elements are embedded in the stainless steel to form a dense alloy layer, which improves corrosion resistance and toughness, and reduces the generation of hydrogen through the hydrogen absorption effect of tantalum, extending the Vapor chamber life.

Benefits of technology

A thinner and durable average hot plate is achieved, avoiding the problem of falling and corrosion of the coating, extending the service life of the average hot plate, and improving its stability at high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116103554B_ABST
    Figure CN116103554B_ABST
Patent Text Reader

Abstract

The present application provides a stainless steel chromium-tantalum alloy material, a stainless steel soaking plate, and a preparation method and application thereof, wherein the stainless steel chromium-tantalum alloy material comprises a stainless steel substrate and a chromium-tantalum alloy layer; the chromium-tantalum alloy layer comprises: by mass, 40-80% chromium, 0.1-4% tantalum, 10-45% iron, 2-10% nickel, and 0-3% trace metal elements. The present application forms a chromium-tantalum alloy layer by alloying chromium and tantalum with stainless steel, wherein the chromium and tantalum elements are embedded in the surface of the stainless steel, and form an alloy with the iron in the stainless steel to become a part of the stainless steel, thereby avoiding problems such as coating shedding; in addition, the chromium content in the formed alloy layer is greater than or equal to 40%, so that a continuous and dense alloy layer can be formed to wrap the stainless steel substrate, thereby avoiding corrosion caused by reactions with water and air, thereby solving problems such as hydrogen evolution in the stainless steel soaking plate by reaction with water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of stainless steel vapor chambers, and in particular to a stainless steel chromium-tantalum alloy material, a stainless steel vapor chamber, and a preparation method and application thereof. Background Art

[0002] With the high integration of electronic devices, there will inevitably be heat dissipation problems of electronic products in small spaces, and heat spreaders have become a popular choice for heat dissipation of electronic products. At present, heat spreaders are basically made of copper or copper alloys, but the heat spreaders made of these materials have low hardness and the thickness is difficult to be less than 0.25mm. However, as electronic products such as mobile phones develop in the direction of ultra-thinness, thinner heat spreaders are needed to meet the demand. In addition, due to the poor corrosion resistance of copper or copper alloys, the heat spreader will oxidize after a period of use, causing further corrosion of the copper or copper alloy, and eventually leading to leakage of the heat spreader liquid and scrapping of electronic products.

[0003] Compared with copper, stainless steel not only has high hardness, good strength, and strong corrosion resistance, but also has obvious cost advantages. However, stainless steel and the working fluid water in the heat spreader will produce hydrogen evolution reaction, resulting in the production of non-condensable gas, which will cause the vacuum degree inside the heat spreader to be significantly reduced, resulting in the failure of the heat spreader. Traditional methods to solve the compatibility of stainless steel with water include electroplating of copper or copper alloys, surface passivation treatment, etc. Due to the poor plating ability of stainless steel, the electroplating process is prone to problems such as coating shedding; the passivation film formed by surface passivation is difficult to withstand the influence of subsequent welding high temperature.

[0004] At the same time, during the laser welding process, there is an inevitable risk of passivation layer failure at the weld. During long-term use, the weld and its surrounding areas may react with water to produce hydrogen, causing the temperature equalizer to fail prematurely. Summary of the invention

[0005] In view of the above-mentioned technical limitations, the present application proposes a stainless steel chromium-tantalum alloy material, a stainless steel soaking plate and its preparation method and application; the present application forms a chromium-tantalum alloy layer by alloying chromium and tantalum with stainless steel, and the chromium and tantalum elements are embedded in the surface of the stainless steel to form an alloy with the iron in the stainless steel, becoming a part of the stainless steel, thereby avoiding problems such as coating shedding; in addition, the chromium content in the formed alloy layer is greater than or equal to 40%, so that a continuous and dense alloy layer can be formed to wrap the stainless steel substrate, thereby avoiding corrosion caused by reaction with water and air, thereby solving the problem of hydrogen evolution in the stainless steel soaking plate. At the same time, the tantalum in the surface alloy layer is a hydrogen-absorbing element, and a certain amount of tantalum can absorb a small amount of hydrogen generated by laser welding, greatly improving the life of the soaking plate.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] The invention of the present application is to provide a stainless steel chromium-tantalum alloy material, comprising a stainless steel substrate and a chromium-tantalum alloy layer; the chromium-tantalum alloy layer comprises: by mass, 40-80% chromium, 0.1-4% tantalum, 10-45% iron, 2-10% nickel, and 0-3% trace metal elements.

[0008] Optionally, the chromium-tantalum alloy layer has a thickness of 0.1 μm to 30 μm.

[0009] Another inventive point of the present application is to provide a method for preparing a stainless steel chromium-tantalum alloy material.

[0010] Optionally, the preparation method includes: in a hydrogen atmosphere, alloying a stainless steel material and a mixed material to obtain the stainless steel chromium-tantalum alloy material; the mixed material includes: by mass, 10 to 70 parts of chromium chloride, 1 to 5 parts of tantalum pentachloride, and 20 to 60 parts of a dispersant.

[0011] Optionally, the alloying conditions are: temperature of 900 to 1050° C.; and time of 3 to 15 hours.

[0012] Optionally, the temperature of the alloy is increased in a gradient manner and is divided into three stages, namely the first stage, the second stage and the third stage; the temperature of the first stage is 450-500°C, and the insulation time is 30min-60min; the temperature of the second stage is 732-850°C, and the insulation time is 30min-60min; the temperature of the third stage is 900-1050°C, and the insulation time is 3-15 hours.

[0013] Optionally, the dispersant includes at least one of aluminum oxide, silicon oxide and magnesium oxide.

[0014] Another inventive point of the present application is to provide an application of the stainless steel chromium-tantalum alloy material as described above in a stainless steel heat sink.

[0015] Another inventive point of the present application is to provide a stainless steel heat sink, comprising a stainless steel alloy cover and a capillary wick; the capillary wick is located between two stainless steel alloy covers; optionally, the stainless steel alloy cover is processed from the stainless steel chromium-tantalum alloy material described above, or the stainless steel cover is alloyed by the preparation method described above to obtain the stainless steel alloy cover.

[0016] Optionally, the preparation method of the stainless steel heat spreader includes: (1) alloying a stainless steel cover and a mixed material in a hydrogen atmosphere to obtain a stainless steel alloy cover; (2) performing a heat preservation treatment at 150°C to 250°C for not less than 1 hour within 4 hours after the stainless steel alloy cover is taken out of the furnace; (3) joining and welding the stainless steel alloy cover and the capillary wick, and then shaping them to obtain a stainless steel heat spreader shell; (4) injecting liquid into the stainless steel heat spreader shell and evacuating the vacuum to obtain the stainless steel heat spreader.

[0017] Optionally, the preparation method of the stainless steel heat spreader includes: (1) alloying a stainless steel material and a mixed material in a hydrogen atmosphere to obtain the stainless steel chromium-tantalum alloy material; (2) processing the stainless steel chromium-tantalum alloy material to obtain a stainless steel alloy cover; (3) combining the stainless steel alloy cover and the capillary core, and then sealing and welding them with another stainless steel alloy cover to obtain a shell containing the capillary core; (4) injecting liquid into the shell containing the capillary core and evacuating the shell to obtain the stainless steel heat spreader.

[0018] Another inventive point of the present application is to provide an application of the stainless steel vapor chamber as described above in electronic products.

[0019] Compared with the prior art, this application has the following advantages:

[0020] (1) The stainless steel chromium-tantalum alloy material of the present application is prepared by alloying chromium and tantalum in the area near the surface of the stainless steel. The chromium and tantalum elements are infiltrated into the surface of the stainless steel to fill the lattice voids of the iron element in the stainless steel, thereby forming a dense alloy layer. In addition, the chromium content is above 40%, which can form a continuous chromium layer, and the addition of tantalum forms a tantalum-chromium-iron alloy, thereby significantly improving the corrosion resistance, toughness and ductility of the material.

[0021] (2) The preparation method of the stainless steel chromium-tantalum alloy material in the present application is to infiltrate the chromium and tantalum in the mixed material into the stainless steel by hydrogen infiltration. The hydrogen can remove the oxide film on the surface of the stainless steel, chromium and tantalum, and under high temperature conditions, chromium chloride and tantalum pentachloride release active chloride ions to promote the activation of chromium and tantalum, and further promote the infiltration of tantalum, thereby generating a stable tantalum-chromium-iron intermetallic compound.

[0022] (3) The stainless steel chromium-tantalum material is used in the stainless steel heat spreader to become the upper cover and lower cover material of the stainless steel heat spreader. Since the stainless steel chromium-tantalum material has excellent corrosion resistance, it will not be corroded by water even if it is in contact with water for a long time, thereby affecting the vacuum degree, heat dissipation performance and service life of the heat spreader. In addition, the filling of chromium and tantalum in the stainless steel chromium-tantalum material with the iron structure makes the overall structure more compact and greatly reduces its expansion coefficient. During use, it can avoid the change of the size of the stainless steel heat spreader caused by factors such as high temperature, thereby affecting its use. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Appearance diagram of the stainless steel upper cover provided for Test Example 1 of this application;

[0024] Figure 2 Appearance diagram of the stainless steel lower cover provided for Test Example 1 of this application;

[0025] Figure 3 This is a scanning electron microscope image of a cross section of a stainless steel soaking plate provided in Experimental Example 1 of this application;

[0026] Figure 4 This is the infrared thermal imaging image of the stainless steel heat sink after aging provided in Experimental Example 1 of this application. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below. However, it should be understood that the description here is only used to explain the present application and is not used to limit the scope of the present application.

[0028] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The raw materials and instruments used in this application are all commercially available, and the characterization methods involved can refer to the relevant descriptions in the prior art, which will not be repeated herein.

[0029] In order to further understand the present application, the present application is further described in detail below in conjunction with the best embodiment.

[0030] Example 1

[0031] The present embodiment provides a stainless steel chromium-tantalum alloy material, including a stainless steel substrate and a chromium-tantalum alloy layer; the chromium-tantalum alloy layer includes: by mass, 40-80% chromium, 0.1-4% tantalum, 10-45% iron, 2-10% nickel, and 0-3% trace metal elements.

[0032] Although chromium can inhibit the reaction between iron ions in stainless steel and water, the chromium alloy layer at the weld will be destroyed during the welding process of the stainless steel heat-absorbing plate, resulting in the risk of reaction with water in this area, making it difficult to meet the long-life requirement of more than 10 years. The iron ions in stainless steel and water mainly undergo hydrogen evolution reaction to produce hydrogen, resulting in a decrease in the vacuum degree inside the heat-absorbing plate. Tantalum is an important hydrogen-absorbing element. When a small amount of tantalum is contained on the surface of stainless steel, it can react with hydrogen to convert hydrogen into hydrogen atoms and fix them in the tantalum metal. In this way, the hydrogen generated by the reaction can be eliminated, thereby greatly extending the service life.

[0033] In the chromium-tantalum alloy layer, the mass content of chromium can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value between any two values.

[0034] The trace metal elements include any one of molybdenum, manganese, vanadium, titanium, aluminum, cobalt and barium.

[0035] The thickness of the chromium-copper alloy layer is 0.1μm to 30μm, for example, it can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 25μm, 30μm or any value between any two values.

[0036] If the thickness is less than 0.1 micron, it is difficult to form a completely continuous alloy layer. Once the alloy layer is discontinuous, structural gaps will appear in the alloy layer, allowing water or air to enter, causing corrosion. If the thickness is greater than 20 microns, on the one hand, the surface brittleness will increase rapidly, resulting in a decrease in the overall material toughness and reduced machinability, which is not conducive to the subsequent change of the shape of the stainless steel chromium-tantalum alloy material. On the other hand, too thick an alloy layer will affect subsequent applications in various electronic devices that require smaller sizes.

[0037] Example 2

[0038] This embodiment provides a method for preparing a stainless steel chromium-tantalum alloy material. The stainless steel chromium-tantalum alloy material is the same as the stainless steel chromium-tantalum alloy material in Example 1, so it is not described here in detail.

[0039] The preparation method comprises: performing alloy treatment on a stainless steel material and a mixed material in a hydrogen atmosphere to obtain the stainless steel alloy material.

[0040] The mixed material covers at least one side of the stainless steel material, and after alloy treatment, at least one side of the stainless steel material contains a chromium-tantalum alloy layer.

[0041] It is preferred that the stainless steel material is completely embedded in the mixed material, that is, each surface of the stainless steel material may contain a chromium-tantalum alloy layer.

[0042] The mixed material is in powder form, and the particle size is preferably less than 50 mesh, more preferably 80-200 mesh. This particle size can ensure that the powder can fully contact and react with the stainless steel surface, and can also prevent the powder from being easily sintered and agglomerated due to the particle size being too fine, which affects the use.

[0043] The mixed material comprises: by mass, 10 to 70 parts of chromium chloride, 1 to 5 parts of tantalum pentachloride and 20 to 60 parts of dispersant.

[0044] Among them, chromium chloride can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts or any value between any two values; dispersant can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any value between any two values; tantalum pentachloride can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts

[0045] Or any value between any two values.

[0046] The alloy conditions are as follows: temperature of 900-1050°C, which may be 900°C, 950°C, 1000°C, 1050°C; time of 3-15 hours, which may be 3 hours, 6 hours, 9 hours, 12 hours or 15 hours.

[0047] The chromium-tantalum infiltration process is carried out at 900℃~1050℃. In a hydrogen atmosphere, chromium chloride reacts with hydrogen to generate hydrogen chloride and active chromium. Hydrogen chloride reacts quickly with the oxide on the surface of the stainless steel to be infiltrated under high temperature conditions and is discharged with the flowing hydrogen. At this time, active chromium is easily adsorbed to the surface of the stainless steel. As the insulation time increases, it diffuses and reacts with the stainless steel, thereby forming a high chromium alloy layer on the stainless steel surface. At the same time, tantalum pentachloride reacts with hydrogen at 900℃~1050℃. The generated active tantalum atoms are deposited on the surface of the substrate to form an alloy layer. It should be noted that the infiltration of chromium and tantalum is almost simultaneous, but the infiltration rate of chromium is much higher than that of tantalum.

[0048] The lattice type of chromium metal is a body-centered cubic structure, and its atomic radius is 0.1249nm; the unit cell of tantalum metal is a body-centered cubic unit cell, and its atomic radius is 0.146nm; the main component of stainless steel is iron, and the lattice type of iron is a body-centered cubic structure when the temperature is less than 900℃, and its atomic radius is 0.1241nm; the lattice type of iron is a face-centered cubic structure when the temperature is between 900℃ and 1394℃, and its atomic radius is 0.1288nm.

[0049] The chromizing process is carried out at a temperature greater than 900°C. At this time, chromium has a body-centered cubic structure with an atomic radius of 0.1249nm, and the free iron ions have a face-centered cubic structure with an atomic radius of 0.1288nm. The high-temperature atomic radii of chromium and iron are relatively close. Under high-temperature conditions, chromium and iron are easy to form a substitutional solid solution. As the insulation time increases, chromium continues to penetrate, and the chromium content also continues to increase.

[0050] When the stainless steel soaking plate is sealing the water inlet, the local temperature at the welding point can reach above 1300℃. Under high temperature conditions, the stainless steel metal easily reacts with water to generate metal oxides and hydrogen. Once hydrogen is formed, a large cold zone will exist inside the stainless steel soaking plate, resulting in performance degradation. Tantalum metal is a hydrogen-absorbing element. A small amount of tantalum on the surface of stainless steel can absorb hydrogen generated by the reaction caused by laser welding or other welding methods, thereby avoiding the formation of cold zones and greatly improving the temperature uniformity of the stainless steel soaking plate.

[0051] After chromizing, the iron will transform from a face-centered cubic structure to a body-centered cubic structure during the cooling process, and the volume will expand. Due to the "anchoring" effect of chromium atoms and tantalum atoms at this time, the volume expansion during the cooling process is limited, and the final chromized layer structure is a uniform and dense structure, which can prevent water and water vapor from penetrating into the matrix and reacting with the free iron ions in the matrix.

[0052] The temperature of the alloy is increased in a gradient manner and is divided into three stages, namely, the first stage, the second stage and the third stage.

[0053] The temperature of the first stage is 450-500°C, and the holding time is 30-60 minutes. In this stage, hydrogen removes the oxide film in the stainless steel material and the mixed material, exposing the metal to prepare for the next step of infiltration. The heating rate in this stage should not be too fast, but should be slowly heated, preferably less than 5°C / min, so that the hydrogen can fully react with the oxide film layer during the slow heating process to remove the oxide film.

[0054] The temperature of the second stage is 732-850℃, and the holding time is 30-60min. This stage is to generate active ions. Both chromium chloride and tantalum pentachloride can generate active chloride ions, and at the same time generate vaporized tantalum, which is convenient for tantalum to penetrate into the stainless steel surface. The heating rate is less than 10℃ / min to prevent the active chloride ions from being quickly extracted, and to maximize the contact with chromium to promote its activation.

[0055] The temperature of the third stage is 900-1050°C, and the holding time is 3-15 hours; during this process, the active chloride ions continuously activate the chromium, and the tantalum vaporized in the second stage infiltrates together.

[0056] The dispersant includes at least one of aluminum oxide, silicon oxide, and magnesium oxide.

[0057] This embodiment provides an application of the stainless steel chromium-tantalum alloy material described above in a stainless steel soaking plate.

[0058] The stainless steel chromium-tantalum alloy material can be processed into different shapes according to the actual application scenarios, for example, it can be a stainless steel heat sink.

[0059] Example 3

[0060] This embodiment provides a stainless steel vapor chamber, which includes a stainless steel alloy cover and a capillary wick; the capillary wick is located between two stainless steel alloy covers.

[0061] The stainless steel alloy cover is obtained by processing the stainless steel chromium-tantalum alloy material described above, or the stainless steel cover is alloyed by the preparation method described above to obtain the stainless steel alloy cover.

[0062] The preparation method of a stainless steel vapor chamber comprises: (1) alloying a stainless steel cover and a mixed material in a hydrogen atmosphere to obtain a stainless steel alloy cover; (2) performing a heat preservation treatment at 150°C to 250°C for not less than 1 hour within 4 hours after the stainless steel alloy cover is taken out of the furnace; (3) joining and welding the stainless steel alloy cover and a capillary wick, and then shaping them to obtain a stainless steel vapor chamber shell; (4) injecting liquid into the stainless steel vapor chamber shell and evacuating the vacuum to obtain the stainless steel vapor chamber.

[0063] There is no limitation on the preparation method of the stainless steel cover and the capillary core in step (1), which may be a conventional method or a commercially available finished product, and the present application does not make any limitation thereon.

[0064] The stainless steel cover includes a stainless steel upper cover and a stainless steel lower cover. Since the stainless steel upper cover and the stainless steel lower cover have the same composition and similar size but different internal structures, they are collectively referred to as stainless steel covers.

[0065] The stainless steel cover is completely embedded in the mixed material and alloyed.

[0066] Further, it can be a step-by-step alloy, that is, in a hydrogen atmosphere, one or more surfaces of the stainless steel cover are first covered with the mixed material, and alloying is performed, and then the remaining surface of the stainless steel cover is covered with the mixed material, and alloying is performed, and finally a cover containing a chromium-tantalum alloy layer, that is, a stainless steel alloy cover is obtained. The step-by-step alloy can be a one-step alloy, a two-step alloy, or a multi-step alloy, and the step-by-step alloy can be performed according to specific needs.

[0067] The alloying conditions are: temperature of 900 to 1050°C; time of 3 to 15 hours.

[0068] The temperature of the alloy is increased in a gradient manner and is divided into three stages, namely the first stage, the second stage and the third stage; the temperature of the first stage is 450-500°C, and the holding time is 30min-60min; the temperature of the second stage is 732-850°C, and the holding time is 30min-60min; the temperature of the third stage is 900-1050°C, and the holding time is 3-15 hours.

[0069] The purpose of the heat preservation treatment in step (2) is to remove the hydrogen adsorbed during the alloying process in time to prevent the occurrence of "hydrogen embrittlement" and other phenomena; the heat preservation treatment is carried out within 4 hours to prevent hydrogen from penetrating into the interior of the stainless steel alloy cover, which makes it more difficult to remove the hydrogen and affects the performance of the stainless steel alloy cover.

[0070] The capillary wick is made of stainless steel and / or copper.

[0071] When the material of the capillary wick is copper, it can be specifically a porous metal material such as copper or copper alloy mesh, foam metal, copper powder sintered porous copper foil, etc.

[0072] When the capillary core is made of stainless steel, the capillary core includes a stainless steel substrate and a chromium-tantalum alloy embedded in the stainless steel substrate; that is, the capillary core made of stainless steel is also alloyed so as to have the same alloy layer as the stainless steel alloy cover. When the two are welded, the instability of the interface is reduced, the two are more easily integrated, gaps are reduced, leakage is avoided, and poor sealing is reduced, thereby extending the service life of the heat spreader.

[0073] The stainless steel cover and capillary core can be made of 304, 304L, 316, 316L. The capillary core can be made of stainless steel wire mesh, copper wire mesh or foam copper with a mesh size less than 80.

[0074] The step (3) of joining the sheets includes: completely fitting the capillary core and the lower cover together. Further, in order to improve the bonding strength, a welding process can be further used to achieve this.

[0075] The welding in step (3) is laser welding; laser welding is efficient, highly reliable and low cost, and is convenient for large-scale use.

[0076] The upper cover and the lower cover are edge-sealed by laser welding, and the laser welding process parameters are: power 20-500W, which can be 20W, 40W, 60W, 80W, 100W, 200W, 300W, 400W or 500W; speed 20-300m / S, which can be 20m / S, 50m / S, 100m / S, 150m / S, 200m / S or 300m / S.

[0077] At present, there is another welding method called brazing, but the brazing process is complicated and the cost is high. The use of brazing will cause the cost to rise sharply. In addition, the bonding strength of the brazed joint is the weakest point in the entire temperature plate. During long-term use, it is very easy to leak and react at the brazing joint. Laser welding does not introduce new materials, and the welding strength is much higher than brazing. At the same time, laser welding also has a series of advantages such as fast speed, low cost, and high yield.

[0078] At present, most of them use copper-plated stainless steel, that is, one or more layers of copper are plated on the surface of stainless steel to avoid contact between water and stainless steel. However, laser welding cannot be used for materials with copper-plated surfaces, that is, laser welding cannot weld materials with high copper content on the surface, because large deformation will occur, resulting in serious distortion of the entire temperature-averaging board. This greatly increases the cost of welding to a certain extent.

[0079] After laser welding, the stainless steel soaking plate is subjected to high-temperature shaping. The shaping temperature is between 880℃ and 1000℃, which can be 880℃, 900℃, 920℃, 940℃, 960℃, 980℃ or 1000℃. The shaping time is greater than 10 minutes, and the flatness of the stainless steel soaking plate after shaping is less than 0.2. Through shaping, the combination of chromium and copper with stainless steel can be better, and the weldability can also be promoted, making the weld stronger. In addition, welding will cause the alloy layer at the weld to be destroyed, and shaping can evenly distribute the destroyed alloy layer elements again and re-form the alloy layer.

[0080] Afterwards, connect the mouse tail, inject water, and vacuum seal.

[0081] The liquid injection tube is used for water injection, vacuuming, sealing and other processes; subsequent shaping and other processes are used to obtain the final stainless steel heat sink product.

[0082] The preparation method of the stainless steel heat spreader comprises: (1) alloying a stainless steel material and a mixed material in a hydrogen atmosphere to obtain the stainless steel chromium-tantalum alloy material; (2) processing the stainless steel chromium-tantalum alloy material to obtain a stainless steel alloy cover; (3) combining the stainless steel alloy cover and a capillary wick, and then sealing and welding the stainless steel alloy cover with another stainless steel alloy cover to obtain a shell containing a capillary wick; (4) injecting liquid into the shell containing the capillary wick and evacuating the shell to obtain the stainless steel heat spreader.

[0083] The method comprises the following steps: firstly obtaining a stainless steel chromium-tantalum alloy material, and then processing the stainless steel chromium-tantalum alloy material into the required shape of a heat spreader, namely, an upper cover and a lower cover of the heat spreader, and then performing processes such as assembly and welding to finally obtain a stainless steel heat spreader.

[0084] Preferably, the stainless steel alloy cover is subjected to a heat preservation treatment at 150° C. to 250° C. for not less than 1 hour within 4 hours after being taken out of the furnace.

[0085] In this method, the method of processing the stainless steel chromium-tantalum alloy material into the upper cover and the lower cover of the heat sink can be any conventional method on the market, and no further limitation is made here.

[0086] The parameters of other processes in this method can refer to the preparation method parameters of Example 2.

[0087] Example 4

[0088] According to the content of this application, the preparation method of the stainless steel chromium-tantalum alloy material of Example 1 and the stainless steel chromium-tantalum alloy material of Example 2 and the heat sink of Example 3 are specifically described, and the specific description is as follows:

[0089] Test Example 1

[0090] (1) Use 0.15 mm thick 316L stainless steel to etch out the stainless steel upper cover and stainless steel lower cover respectively. Figure 1 and Figure 2 As shown, Figure 1 It is the upper cover, and the middle convex point is the supporting column; Figure 2 The lower cover has a groove structure in the middle for placing the capillary core (the stainless steel upper cover and stainless steel lower cover of other test examples are the same as Figure 1 and Figure 2 are of the same shape);

[0091] (2) placing the stainless steel upper cover and the stainless steel lower cover together with the mixed materials (30 parts of 80-mesh chromium chloride, 3 parts of 80-mesh tantalum pentachloride, and 30 parts of 80-mesh alumina powder) in a furnace pot to fully cover the stainless steel upper cover and the stainless steel lower cover; then introducing hydrogen with a purity greater than 98% until the air in the furnace pot is driven out and exhausted, and then starting to heat up at a heating rate of 3°C / min. When the temperature reaches 450°C, keep it warm for 55 minutes; then continue to heat up at a heating rate of 8°C / min. When the temperature reaches 750°C, keep it warm for 50 minutes; then continue to heat up at a heating rate of 10°C / min. When the temperature reaches 930°C, keep it warm for 10 hours; after cooling to room temperature, take out the stainless steel alloy upper cover and the stainless steel alloy lower cover;

[0092] (3) Immediately place the stainless steel alloy upper cover and the stainless steel alloy lower cover at 200°C for 2 hours to remove hydrogen;

[0093] (4) Cut a 325 mesh copper mesh and fix it in the stainless steel alloy lower cover, and then perform laser sealing welding with the stainless steel alloy upper cover. The laser welding process parameters are: power 100W, speed 80m / s, and a shell containing a capillary core is obtained. The shell after welding is subjected to high temperature shaping, the shaping temperature is 910℃ and the holding time is 30 minutes. The flatness of the stainless steel heat plate after shaping is 0.08;

[0094] (5) Then perform vacuuming, water injection, sealing, and nozzle cutting operations to obtain a stainless steel soaking plate.

[0095] The average values ​​of the elements and contents in the chromium-tantalum alloy layer are: chromium 65%, tantalum 1.2%, iron 25%, nickel 6%, trace elements (molybdenum, etc.) 2.8%, and the thickness of the chromium-tantalum alloy layer is 6 microns; Figure 3 As shown, the chromium-tantalum alloy layer formed on the surface of the stainless steel substrate is dense and smooth, which can effectively prevent other substances from corroding the stainless steel, thereby improving the corrosion resistance of the stainless steel and further increasing the service life of the stainless steel soaking plate.

[0096] Test Example 2

[0097] (1) A stainless steel upper cover and a stainless steel lower cover are etched out using 316L stainless steel with a thickness of 0.2 mm and 0.1 mm respectively;

[0098] (2) placing the stainless steel upper cover and the stainless steel lower cover together with the mixed materials (50 parts of 80-mesh chromium chloride, 4 parts of 80-mesh tantalum pentachloride, and 50 parts of 80-mesh alumina powder) in a furnace pot to fully cover the stainless steel upper cover and the stainless steel lower cover; then introducing hydrogen with a purity greater than 98% until the air in the furnace pot is driven out and exhausted, and then starting to heat up at a heating rate of 4°C / min. When the temperature reaches 480°C, keep it warm for 34 minutes; then continue to heat up at a heating rate of 5°C / min. When the temperature reaches 780°C, keep it warm for 45 minutes; then continue to heat up at a heating rate of 8°C / min. When the temperature reaches 940°C, keep it warm for 8 hours; after cooling to room temperature, take out the stainless steel alloy upper cover and the stainless steel alloy lower cover;

[0099] (3) Immediately place the stainless steel alloy upper cover and the stainless steel alloy lower cover at 240°C for 1.5 hours to remove hydrogen;

[0100] (4) Cut a 325 mesh copper mesh and fix it in the stainless steel alloy lower cover, and then perform laser sealing welding with the stainless steel alloy upper cover. The laser welding process parameters are: power 120W, speed 60m / S, and a shell containing a capillary core is obtained. The shell after welding is subjected to high temperature shaping, the shaping temperature is 910℃ and the holding time is 30 minutes. The flatness of the stainless steel soaking plate after shaping is 0.08;

[0101] (5) Then perform vacuuming, water injection, sealing, and nozzle cutting operations to obtain a stainless steel soaking plate.

[0102] The average values ​​of the elements and contents in the chromium-tantalum alloy layer are: chromium 68%, tantalum 4%, iron 20%, nickel 6%, trace elements (molybdenum, etc.) 2%, and the thickness of the chromium-tantalum alloy layer is 8 microns.

[0103] Test Example 3

[0104] (1) A stainless steel upper cover and a stainless steel lower cover are etched out of 316L stainless steel with a thickness of 0.15 mm;

[0105] (2) placing the stainless steel upper cover and the stainless steel lower cover together with the mixed materials (40 parts of 80-mesh chromium chloride, 3 parts of 80-mesh tantalum pentachloride, and 60 parts of 80-mesh alumina powder) in a furnace pot to fully cover the stainless steel upper cover and the stainless steel lower cover; then introducing hydrogen with a purity greater than 98% until the air in the furnace pot is driven out and exhausted, and then starting to heat up at a heating rate of 2°C / min. When the temperature reaches 460°C, keep it warm for 40 minutes; then continue to heat up at a heating rate of 9°C / min. When the temperature reaches 830°C, keep it warm for 37 minutes; then continue to heat up at a heating rate of 12°C / min. When the temperature reaches 920°C, keep it warm for 6 hours; after cooling to room temperature, take out the stainless steel alloy upper cover and the stainless steel alloy lower cover;

[0106] (3) Immediately place the stainless steel alloy upper cover and the stainless steel alloy lower cover at 180°C for 3 hours to remove hydrogen;

[0107] (4) Cut a 325 mesh copper mesh and fix it in the stainless steel alloy lower cover, and then perform laser sealing welding with the stainless steel alloy upper cover. The laser welding process parameters are: power 70W, speed 130m / s, and a shell containing a capillary core is obtained. The shell after welding is subjected to high temperature shaping, the shaping temperature is 910℃ and the holding time is 30 minutes. The flatness of the stainless steel heat plate after shaping is 0.08;

[0108] (5) Then perform vacuuming, water injection, sealing, and nozzle cutting operations to obtain a stainless steel soaking plate.

[0109] The average values ​​of the elements and contents in the chromium-tantalum alloy layer are: chromium 57%, tantalum 0.5%, iron 35%, nickel 5%, trace elements (molybdenum, etc.) 2.5%, and the thickness of the chromium-tantalum alloy layer is 2 microns.

[0110] Comparative Example 1

[0111] The method only includes steps (1), (4) and (5) of Test Example 1, i.e., does not include steps (2) and (3). The upper cover and the lower cover of the obtained stainless steel heat sink do not contain a chromium-tantalum alloy layer.

[0112] Performance Testing

[0113] (1) Detect the temperature difference between the two farthest points of the stainless steel heat spreader prepared above after high-temperature aging. Place the stainless steel heat spreader in an environment of 150°C for 100 hours and measure the temperature difference between the two points of the heat spreader. The specific test method is: 5W test power, before the aging test, the test temperatures of the two points are T1 and T2 (the heat source is below the heat spreader, and the test thermocouple is above the heat spreader), after aging at 150°C for 100 hours, the test temperatures of the two points are T1' and T2'. If the difference between T1 and T1', T2 and T2', and T1 and T2 is not significantly different from the difference between T1' and T2', it is considered that the performance of the heat spreader has basically not changed, that is, no reaction has occurred inside. The results are shown in Table 2.

[0114] The purpose of high-temperature aging is to determine whether a reaction occurs between water vapor and the inner cavity material. If a reaction occurs, the performance after aging will be significantly attenuated, causing the temperature of the heat spreader to change greatly before and after, and the temperature will drop, which will significantly reduce its heat conduction performance.

[0115] Table 2 Performance test results of stainless steel soaking plates of test examples and comparative examples

[0116] T1(℃) T2(℃) T1-T2(℃) T1’(℃) T2’(℃) T1'-T2'(℃) Test Example 1 67.2 65.9 1.3 67.1 65.7 1.4 Test Example 2 66.9 65.3 1.6 67.0 65.5 1.5 Test Example 3 67.5 65.1 2.4 67.4 64.9 2.5 Comparative Example 1 67.2 65.0 2.2 85.2 53.0 32.2

[0117] As shown in Table 2, the temperature difference before and after aging at 150°C for 100 hours is almost unchanged, indicating that no hydrogen evolution reaction occurs inside. This proves that the temperature equalization plate described in this patent has a long service life. However, the temperature difference of the sample without surface treatment in the control example exceeded 30°C after aging, and it has already failed.

[0118] The comparison of the above values ​​shows that the addition of chromium and tantalum can avoid the reaction between water and stainless steel, thereby better protecting the stainless steel and maintaining the heat dissipation of the bipolar plate.

[0119] The stainless steel soaking plate of the above-mentioned aged test example 1 was tested again, the test power was 4W, and the other parameters were the same as the above test method; during the test, infrared thermal imaging was performed on the stainless steel soaking plate, and three positions were randomly selected to display their temperatures. The results are shown in Figure 4 .

[0120] like Figure 4 As shown, the three positions Ar1, Ar2 and Ar3 are located at the upper left, middle and lower right parts of the heat spreader respectively, and the selection of these three positions can represent the overall temperature of the heat spreader; the temperatures of the three positions Ar1, Ar2 and Ar3 are 49.0°C, 49.1°C and 49.3°C respectively, and the maximum temperature difference is 0.3°C, indicating that the heat spreader can still maintain excellent heat dissipation performance after aging, and it can also be explained that no hydrogen evolution reaction occurs inside the heat spreader, which further proves that the penetration of chromium and tantalum has a protective effect on stainless steel.

[0121] (2) At the same time, the state of the iron element in the alloy layer was tested. When free iron exists, the free iron is easy to react with water. The test method is the blue dot test, which is: use 5 grams of potassium ferrocyanide K3[Fe[CN]6], add 1 milliliter of 98% sulfuric acid and 5 milliliters of 36% hydrochloric acid, add appropriate amount of distilled water to prepare a solution with a total volume of 100 milliliters (prepared immediately); directly apply or drip the solution on the upper cover of the test example and the comparative example, and observe the appearance of blue dots, that is, whether blue dots appear and when they appear. It should be noted that this test needs to be carried out after the pickling and passivation surface is basically dry. The test liquid should be rinsed clean after the test.

[0122] The basic principle of the blue dot test is that if the surface passivation film is imperfect or there is ferrous ion contamination, ferrous ions will be present, and the following reaction can occur;

[0123] 3Fe2 + +2[Fe[CN6]] - =Fe3[Fe[CN]6]2 dark blue precipitate can be used to test whether passivation treatment has been performed and to test the passivation effect.

[0124] Among them, the time for blue spots to appear on the untreated upper cover in Comparative Example 1 is 12 minutes, indicating that there is a certain amount of free iron therein, while the upper cover containing the chromium-tantalum alloy layer in Test Examples 1 to 3 of the present application has not shown blue spots after 24 hours, indicating that the amount of free iron in the alloy layer is almost non-existent, and an alloy layer is formed with chromium and tantalum, thus having better anti-corrosion performance.

[0125] (3) According to the life prediction experience of traditional heat pipe accelerated aging tests, the heat spreaders prepared in Test Examples 1 to 3 of the present application showed no performance degradation after aging at 150°C for 100 hours, indicating that the stainless steel heat spreaders of the present application have a long service life. Therefore, the heat spreaders of the present application can be used not only in mobile phones, but also in other heat dissipation components with long life requirements.

[0126] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A stainless steel chromium-tantalum alloy material, characterized in that: including a stainless steel substrate and a chromium-tantalum alloy layer; The chromium-tantalum alloy layer comprises, by mass, 40-80% chromium, 0.1-4% tantalum, 10-45% iron, 2-10% nickel, and 0-3% trace metal elements; the trace metal elements include any one of molybdenum, manganese, vanadium, titanium, aluminum, cobalt, and barium; The thickness of the chromium-tantalum alloy layer is 0.1 μm to 30 μm; The chromium element and the tantalum element are embedded in the surface of the stainless steel, form an alloy with the iron in the stainless steel, and become a part of the stainless steel.

2. A method for preparing the stainless steel chromium-tantalum alloy material according to claim 1, characterized in that: In a hydrogen atmosphere, alloying the stainless steel material and the mixed material to obtain the stainless steel chromium-tantalum alloy material; The mixed material comprises: by mass, 10 to 70 parts of chromium chloride, 1 to 5 parts of tantalum pentachloride, and 20 to 60 parts of a dispersant.

3. The method according to claim 2, characterized in that The alloying conditions are: temperature of 900~1050°C; time of 3~15 hours.

4. The method according to claim 3, characterized in that The alloying temperature is a gradient heating, which is divided into three stages, namely the first stage, the second stage and the third stage; The temperature of the first stage is 450~500℃, and the holding time is 30min~60min; The temperature of the second stage is 732~850℃, and the holding time is 30min~60min; The temperature of the third stage is 900~1050℃, and the insulation time is 3~15 hours.

5. The method according to claim 2, characterized in that: The dispersant includes at least one of aluminum oxide, silicon oxide and magnesium oxide.

6. Application of the stainless steel chromium-tantalum alloy material according to claim 1 in a stainless steel soaking plate.

7. A stainless steel soaking plate, characterized in that: It comprises a stainless steel alloy cover and a capillary core; the capillary core is located between two stainless steel alloy covers; The stainless steel alloy cover is obtained by processing the stainless steel chromium-tantalum alloy material according to claim 1, or the stainless steel cover is obtained by alloying the stainless steel cover according to any one of claims 2 to 5.

8. The stainless steel soaking plate according to claim 7, characterized in that: The preparation method of the stainless steel soaking plate comprises: (1) In a hydrogen atmosphere, alloying the stainless steel cover and the mixed material to obtain a stainless steel alloy cover; (2) Within 4 hours after the stainless steel alloy cover is taken out of the furnace, it shall be subjected to heat preservation treatment at 150℃~250℃ for not less than 1 hour; (3) The stainless steel alloy cover and the capillary wick are assembled, welded, and then shaped to obtain a stainless steel heat sink shell; (4) Liquid is injected into the shell of the stainless steel heat spreader and vacuum is evacuated to obtain the stainless steel heat spreader.

9. The stainless steel soaking plate according to claim 7, characterized in that: The preparation method of the stainless steel soaking plate comprises: (1) alloying the stainless steel material and the mixed material in a hydrogen atmosphere to obtain the stainless steel chromium-tantalum alloy material; (2) Processing the stainless steel chromium-tantalum alloy material to obtain a stainless steel alloy cover; (3) After the stainless steel alloy cover and the capillary core are assembled, they are sealed and welded with another stainless steel alloy cover to obtain a shell containing the capillary core; (4) The shell containing the capillary core is injected with liquid and evacuated to obtain the stainless steel heat sink.

Citation Information

Patent Citations

  • Medium carbon CrNiMo steel surface chromium-tantalum gradient coating and preparation method thereof

    CN104818483A

  • Ultrathin vapor chamber, preparation method thereof and electronic equipment

    CN113498295A

  • Stainless steel object having a surface modified with chromium

    WO2020053443A1